Polytechnics as Institutions for Intraregional Collaboration for Skills Development in Africa - F., Kutsanedzie; ., Mensah E. (Journal of Education and Vocational Research, 2013)
The Polytechnics in Ghana were established and given the mandate enshrined in the Constitution of Ghana under the Act of Parliament of the Republic of Ghana (Act 745) to train students in the fields of Science, Technology, Applied Social Science and Applied Art to serve the middle-manpower management needs of the country. In addition, the polytechnics are to provide skills development, conduct and publish industry driven research findings. Polytechnic graduate are expected by employers and captains of industry to be more practical-skilled and biased by virtue of their training. However, over the years, it appears the polytechnic graduate training is becoming more of theoretical rather than what was initially intended. Commentaries of stakeholders reveal that the polytechnics are gradually losing their focus vis-à-vis the practical training of students as they are fast comparing themselves to the universities. This paper uses observation of the polytechnics educational system, interviews with stakeholders and other secondary data as the bases to critically examine and identify the conditions that hamper the practical training of the polytechnic students – practical content of syllabi; teacher – student ratio in the face of high student intake; qualification of lecturers in terms of practical training. It thus recommends ways by which the polytechnics can improve upon the practical training of its student via mobilizing and utilizing its resources to create industries to facilitate the training of its students as well as reducing graduate unemployment. This thus will serve as lynch-pin to drive the country’s industrialization process.